2007
DOI: 10.1115/1.2748465
|View full text |Cite
|
Sign up to set email alerts
|

A State-Switched Absorber Used for Vibration Control of Continuous Systems

Abstract: A state-switched absorber (SSA) is a device that is capable of switching between discrete stiffnesses; thus, it is able to instantaneously switch between resonance frequencies. The state-switched absorber is essentially a passive vibration absorber between switch events; however, at each switch event the SSA instantly “retunes” its natural frequency and maintains that frequency until the next switch event. This paper considers the optimization of the state-switched absorber applied to a continuous vibrating sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…This change may be controlled as necessary or desired via a control algorithm applied through a processor. A number of research groups were focused on such applications, for example, Albanese [46] and Holdhusen [47] presented MRE absorbers working in a compression mode. Deng et al [11,48], Zhang and Li [14] presented MRE absorbers worked in a shear mode.…”
Section: Tunable Dynamic Vibration Absorbersmentioning
confidence: 99%
“…This change may be controlled as necessary or desired via a control algorithm applied through a processor. A number of research groups were focused on such applications, for example, Albanese [46] and Holdhusen [47] presented MRE absorbers working in a compression mode. Deng et al [11,48], Zhang and Li [14] presented MRE absorbers worked in a shear mode.…”
Section: Tunable Dynamic Vibration Absorbersmentioning
confidence: 99%
“…It can address the control of multifrequency excitation. Holdhusen used magneto-rheological elastomers to fabricate an SSA for vibration control of continuous system [21]. The results showed that the SSA was effective over a larger bandwidth than that of a classical tuned vibration absorber.…”
Section: Introductionmentioning
confidence: 97%
“…designed a kind of tension–compression DVA that uses magnetorheological elastic material as the spring unit to switch between resonance frequencies and the effective bandwidth. 9…”
Section: Introductionmentioning
confidence: 99%